La sobreprotección familiar y el desarrollo integral de los niños de 3 a 5 años en época de pandemia. - Salazar Parra, Cristina Eunice (2022)
In the present investigative work, the incidence of family overprotection in integral child development was addressed as a problem, considering that this style of upbringing harms all areas of children's development, by limiting their access to experiences for learning and socialization. , thus creating dependent, insecure, shy, self-centered children, with problems to respect the rules of coexistence, to socialize and with difficulties in child development indicators. The objective of the research was to determine the incidence of family overprotection in the comprehensive development of children from 3 to 5 years of the Ana Páez Educational Unit, through scientific research to promote a favorable parenting style. For this, a qualitative-quantitative approach methodology was used at a descriptive and correlational level, through the modality of research-action, bibliography and field. The results obtained in the investigation allow to show that the infants present a low level of integral development in the motor, language, cognitive and affective spheres, which is interrelated with the characteristics of overprotection within the families, the techniques used were the interview, survey and observation. For this reason, a training proposal was developed for parents, where through activities and dynamics, awareness was raised about family overprotection and its negative effects on comprehensive child development, which has been favorably evaluated by experts and users. as well as it has generated positive results from its application.